Hydrographic data from the Rio Grande Cone region, southwestern Atlantic Ocean in 2022 - Rafael A Avila; Jose H Muelbert (PANGAEA, 2024)
This dataset contains 12 vertical profiles of eight variables: Temperature, potential temperature, conductivity, salinity, pressure, potential density, fluorescence. All data was obtained during the TRIATLAS-1, carried out from Oct 31 to Nov 9, 2022. The cruise took place in the area of the Rio Grande Cone, an important region in the southwestern Atlantic Ocean regarding sediment transport, biological production and mesoscale circulation. The cruise grid covered an area of approximately 6,500 squared kilometers, from the shelf-break to the open ocean. The cruise goal was to investigate the behavior and abundance of mesopelagic fauna in the Rio Grande Cone region and the potential of this region to be a hot spot for biological production. All data was obtained with a SeaBird SBE 25plus Sealogger CTD (conductivity, temperature and depth) and are properly treated by the manufacturer provided software.